A STUDY ON CONSTRUCTION CLAIMS OF CONSTRUCTION PROJECT IN BANJAR REGENCY - Mursal Mursal (Lambung Mangkurat University Press, 2014)
The competitive atmosphere in winning a construction tender is one of the main considerations of the construction service providers to improve their construction efficiency. This issue indicates that the construction services companies that could improve their efficiency to the fullest are those that could reduce work cost and in turn win the tender. Cost competition due to the efficiency may result in unusually low bid price, thus the construction companies try to look for the opportunities to win the tender by planning claim fillings to ensure the profit for the construction service companies. Nevertheless, contract termination claims toward low bidding tender still occur. This fact indicates that the low bidding tenders were not equipped with construction claim planning. Construction claims to the work contractors occurred in Banjar regency are mainly due to the completion lateness, low work volume, low work quality or defect. Those factors result in either contract termination claim or contract reduced value claim. Research method implemented is to interpret data measurement result to obtain data that can be analyzed descriptively from the data processed to result in alternative consideration in the discussion of construction claim in Banjar regency. The result shows that the kinds of construction claim in Banjar regency year 2012 are time claim, cost claims, work scope claims, combined claims, and contract terminations. The causes of construction claims are work volume addition, less work volume, changes in work design, field condition, completion lateness, and the inability of service companies to finish the construction. The resolutions of the construction claims are by negotiating the completion time, work value addition material specification change approval, and contract termination for the service providers who fail to finish the project in time mentioned in the contract. Contracts with very low tender or fewer than 80^ of the budget ceiling are equipped with construction claim design to avoid contract termination.